The Use of Phyphox Application in Physics Experiments: A Literature Review - Nisrina Imtinan; Heru Kuswanto (STKIP Singkawang, 2023)
Nowadays, the most popular gadget owned by students is a smartphone. The sophistication of smartphones is not only used by students as a communication tool, but also internet browsing, reading e-books, and various other features that can facilitate student activities. In particular, smartphones create conditions for accessing educational programs, scientific materials, and mobile applications for field experiments. Many sensors are integrated in smartphones, thereby adding to the functionality of the smartphone itself. For example, basically every smartphone has an acceleration sensor that is used to determine orientation relative to the acceleration of gravity, a magnetometer to help GPS sensors for navigation, as well as a light sensor and a gyroscope to measure rotational speed. Pressure sensors are also available on some smartphones which can be used as indoor navigation. All of these sensors can be read with the appropriate application and can be used for smartphone-based school experiments, especially in Physics learning. Phyphox is one such sensor reading application that offers many features on it. This study provides reference for the Physics experiments innovation using Phyphox that can also help Physics educational practitioners and researchers to improve the scope and quality of Physics learning programs.